Direct Innominate Artery Cannulation versus Side Graft for Selective Antegrade Cerebral Perfusion during Aortic Hemiarch Replacement - Gergen, Anna K.; Kemp, Cenea; Ghincea, Christian V.; Feng, Zihan; Ikeno, Yuki; Aftab, Muhammad; Reece, T. Brett (AORTA, 2022)
Background Selective antegrade cerebral perfusion (SACP) has become our preferred method for cerebral protection during open arch cases. While the initial approach involved sewing a graft to the innominate artery as the arterial cannulation site, our access strategy has since evolved to central aortic cannulation with use of a percutaneous cannula in the innominate for SACP. We hypothesized that SACP delivered via direct innominate cannulation using a 12- or 14-Fr cannula results in equivalent outcomes to cases utilizing a side graft.Methods This was a single-center, retrospective analysis of 211 adult patients who underwent elective hemiarch replacement using hypothermic circulatory arrest with SACP via the innominate artery between 2012 and 2020. Urgent and emergent cases were excluded.Results A side graft sutured to the innominate was utilized in 81% (n = 171) of patients, while direct innominate artery cannulation was performed in 19% (n = 40) of patients. Baseline patient characteristics were similar between groups aside from a higher baseline creatinine in the direct cannulation group (1.3 vs. 0.9, p = 0.032). Patients undergoing direct cannulation demonstrated shorter cardiopulmonary bypass time (132.7 vs. 154.9 minutes, p = 0.020) and shorter circulatory arrest time (8.1 vs. 10.9 minutes, p = 0.004). Nadir bladder temperature did not significantly differ between groups (27.2°C for side graft vs. 27.6°C for direct cannulation, p = 0.088). There were no significant differences in postoperative outcomes.Conclusion Direct cannulation of the innominate artery with a 12- or 14-Fr cannula for SACP during hemiarch replacement is a safe alternative to using a sutured side graft. While cardiopulmonary bypass and circulatory arrest times appear improved, this is likely attributable to accumulation of experience and proficiency in technique. However, direct innominate artery cannulation may facilitate quicker completion of these procedures by eliminating the time necessary to suture a graft to the innominate artery.
Keywords: hemiarch replacement; selective antegrade cerebral perfusion; hypothermic circulatory arrest; direct cannulation; side graft